Susceptibility of human B lymphocyte cell lines to dialysed latex B- and C- sera fractions - Lam K L; Chai Y L; Chow T W; Ong M T; Sunderasan E; Yang K L (Journal of Rubber Research, 2012)
Hevea brasiliensis latex sera are being investigated for anticancer property. In the present cell based assay, whole latex B- and C- sera were shown to be largely ineffective against human B lymphocytes, of both cancer origin (BDCM) and non-cancer origin (Bristol 8); albeit slight dip in cell viability were discerned at high concentrations (>100mg/mL) of whole C-serum, the retentate of dialysed C-serum, the increment however was more prominant in the dialysed C-serum precipitate (DCP) compared to the dialysed C-serum supernatant (DCS). DCP also showed a marginally higher specificity against BDCM (LC50 = 55.95 Mg/mL) compared to Bristol 8 (LC50 = 75.62 Mg/mL). However in the treatments with the retentate of dialysed B-serum, both BDCM and Bristol 8 cells remained unaffected.
Source Year: 2012
Keywords: Anticancer; Dialysis; Latex B-serum; Latex C-serum; MTS; Suspension cells